Preliminary Discussion on Comprehensive Research Method for Rock Burst in Coal Mine Based on Newton's Second Law. (13th October 2020) - Zuo, Jianping; Song, Hongqiang; Jiang, Yunqian; Zhao, Shankun; Yu, Meilu; Li, Liyun
Abstract : Rock burst is one of the major dynamic disasters that directly threaten production safety in coal mines. According to the current research, the occurrence of rock burst can be described by the generalized Newton's second law with three elements which are research object, force condition, and motion state. These three elements refer to the coal and rock mass in the mining area, concentrated static and dynamic loads, and dynamic instability of surrounding rock, respectively. On this basis, a comprehensive rock burst research method involving the three elements of Newton's second law was proposed, which especially focuses on the investigation into geological conditions of mining areas. The research procedure of this method specifically includes the detailed exploration of engineering geological bodies, the classification and stability evaluation of surrounding rock, the measurement and inversion of in situ stress, the evolution analysis of mining-induced stress field, energy field, and fracture field, the study of multiscale failure mechanism of coal and rock mass, the establishment of theoretical failure model of coal and rock mass, the real-time monitoring and warning in potentially dangerous areas, and the reasonable prevention and control in key risk zones. As a preliminary discussion, the significant research progress in each aspect mentioned above has been reviewed and the feasible research directions of rock burst are presented in this paper.